Analysis of the Compliance of Organic, Inorganic, and Hazardous Waste (B3) Segregation Systems with Waste Management Standards at Siliwangi University - Fahmi Fahrul Rozi; Naisya Rahma Salsabila; Kultsum Chairun Nisa; Andzar Ihsanuddin Sonata; Esta Rendra RS (Jurnal Geografi, Lingkungan dan Kesehatan, 2026)
The increase in academic activity at Siliwangi University has resulted in an increase in the volume of domestic and hazardous waste, requiring systematic management. This study aims to analyze the level of compliance of waste sorting practices with national standards and identify barriers to their implementation. The study used a descriptive qualitative approach. Respondents consisted of cleaning staff and students selected using purposive and stratified random sampling techniques. Data collection was conducted through field observations and in-depth interviews. The results indicate that the implementation of waste sorting at Siliwangi University does not fully comply with national technical standards and Government Regulation No. 22 of 2021. Although basic facilities are available, their distribution is uneven, and container labels are not informative. A behavioral gap was identified among students, where knowledge of waste types is good but not translated into behavior due to practical factors and systemic inefficiencies, where waste is re-mixed during transportation. In conclusion, hazardous waste management has the lowest level of compliance, and system effectiveness still relies heavily on manual sorting at the final stage. Facility standardization, synchronization of the non-mixing transportation system, and strengthening of sustainable campus policies are needed to improve waste management.